Economic Policy Stability, Digital Governance Capability, and Artificial Intelligence Innovation Performance - Rizani, Ahmad; Darsono, Tri; Mohammed Sultan Saif, Gehad (Journal Economic Business Innovation, 2026)
Purpose—This study examines how Economic Policy Stability, Digital Infrastructure Readiness, Research and Development Capability, and Artificial Intelligence Talent Capability influence Artificial Intelligence Innovation Performance. It assesses the mediating role of Digital Governance Capability in Indonesian manufacturing firms. Design/methodology/approach—This study uses a quantitative, explanatory approach grounded in Real Options Theory, Dynamic Capabilities Theory, the National Innovation System Theory, and the Resource-Based View. Data were gathered from 250 respondents in Indonesian manufacturing firms and analyzed with Partial Least Squares Structural Equation Modeling via SmartPLS 4. Findings—The results indicate that Economic Policy Stability, Digital Infrastructure Readiness, Research and Development Capability, and Artificial Intelligence Talent Capability each have a positive and significant impact on Artificial Intelligence Innovation Performance. Additionally, these factors also significantly enhance Digital Governance Capability. Moreover, Digital Governance Capability positively influences Artificial Intelligence Innovation Performance and partially mediates all the relationships proposed. Originality/value—This study advances AI innovation research by integrating policy stability, digital resources, R&D capacity, AI talent, and digital governance into a comprehensive model. It underscores Digital Governance Capability as a key strategic mechanism that converts institutional and organizational strengths into AI-driven innovation results. Implications—The findings indicate that manufacturing companies need to bolster AI innovation not just by investing in technology, but also by ensuring consistent policy support, improving digital infrastructure, advancing R&D, developing AI expertise, and implementing responsible digital governance.